Mā muqīmān : muʾrab - Wiṣālī, ʿAlāʾ-ad-Dīn Ḫurāsānī (Sinṭral Prīzan Pres, 1880)
A Persian strophic poem with mystical content by a disciple of Niẓām-ad-Dīn Awlīyā who came to India from Ḫurāsān and settled in Awadh